Sistem Informasi Monitoring Produk Barang Impor Pada PT. Samudra Permata Motokarz Jakarta - Ade Suryanto; Muhammad Rekza Fauzy (LPPM Universitas Bina Sarana Informatika, 2021)
Export-import activities in this modern era increasingly make it easier for export-importers. Such is the case with the recording of import data at the computerized Customs and Excise Customs Office (KPBC). Make it easy for export-importers to monitor the export-import of their goods. And also other service providers that are interrelated in the export-import process. They have computerized the data, then informed it through the website. So as a service user it is easier to find information related to their export-import goods. In this research a web-based information system is designed. With this system, it is expected to be able to overcome the various needs of users to find information and determine the decisions that will be taken next. Because quick decision making will save costs and make performance more effective and efficient at PT. Samudra Permata Motokarz in the implementation of export-import. And data that has been stored in the database can be an archive that is not easily lost and easy to find in the future if needed.